THE INFLUENCE OF PRINCIPAL LEADERSHIP, COMPETENCE, AND WORK MOTIVATION OF TEACHER ON TEACHER PERFORMANCE AT SMA NEGERI 1 TANAH JAMBO AYEE, DISTRICT ACEH UTARA - Zainuddin Iba; Mukhtar Mukhtar; Kamaruddin Kamaruddin (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This study aims to determine the influence of the principal's leadership, teacher competency and teacher work motivation on teacher performance at SMA Negeri 1 Tanah Jambo Ayee, North Aceh District. This type of research is quantitative and uses causality analysis methods. The population and sample in this study were 86 teachers at SMA Negeri 1 Tanah Jambo Ayee, North Aceh District. The data analysis technique used is path analysis with SPSS. Based on the results of the causality study, it can be concluded that the Principal's Leadership has a significant effect on Teacher Performance by 63.2%. Teacher competence has a significant effect on teacher performance by 63.1%. Teacher Work Motivation has a significant effect on Teacher Performance by 79.9%. The principal's leadership has a significant effect on teacher competency by 72.5%. Principal leadership has a significant effect on teacher work motivation of 83.8%. Teacher competence has a significant effect on teacher work motivation by 73.6%. Principal leadership has a significant effect on teacher performance through teacher competence of 65.7%. Principal leadership has a significant effect on teacher performance through teacher work motivation of 65.8%. Teacher competence has a significant effect on teacher performance through teacher work motivation of 76.2%. Principal Leadership, Teacher Competence, and Teacher Work Motivation have a significant effect on Teacher Performance simultaneously by 59.8%.